2016
DOI: 10.4238/gmr.15028640
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms and haplotype of hormone-related genes are associated with the risk of breast cancer in Chinese women

Abstract: ABSTRACT. Sex hormones play important roles in breast cancer (BC) development. This study investigated associations between BC risk and hormone-related gene variants in Chinese women. In a cohort of 336 patients with histopathologically confirmed BC and 390 age-matched controls, we genotyped seven single nucleotide polymorphisms (SNPs) in five hormone-related genes: estrogen receptor-α (ESR1), aromatase (CYP19), catechol-O-methyl transferase (COMT), sex hormonebinding globulin (SHBG), and glutathione S-transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
7
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
4
7
2
1
Order By: Relevance
“…Previous studies suggested that the functional mutation of the GSTP1 rs1695 polymorphisms may reduce the activity of GST-π enzyme deactivating and detoxifying carcinogens and thus may increase cancer vulnerability (40) . Nevertheless, our data showed no significant association between the GSTP1 homozygous mutant GG genotype and breast cancer risk, which was consistent with a 2016 meta-analysis of thirty-six case-control studies including 20 615 cases and 20 481 controls (19) , and studies from China (39) and Cyprus (41) , but contrary to studies from Shanghai (23) and Zhejiang (38) of China which found that the GSTP1 GG genotype was significantly associated with greater risk of breast cancer (OR 2•23 and 1•50, respectively, GG v. AA). The GSTM1 and GSTT1 null genotypes were prevalent among 60•7 and 16•3 % of controls in the present study, which was consistent with the rate of GSTM1 null genotype (59•1 %), but much lower than that of GSTT1 null genotype (51•9 %) in Shanghai Women's Health Study (42) .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies suggested that the functional mutation of the GSTP1 rs1695 polymorphisms may reduce the activity of GST-π enzyme deactivating and detoxifying carcinogens and thus may increase cancer vulnerability (40) . Nevertheless, our data showed no significant association between the GSTP1 homozygous mutant GG genotype and breast cancer risk, which was consistent with a 2016 meta-analysis of thirty-six case-control studies including 20 615 cases and 20 481 controls (19) , and studies from China (39) and Cyprus (41) , but contrary to studies from Shanghai (23) and Zhejiang (38) of China which found that the GSTP1 GG genotype was significantly associated with greater risk of breast cancer (OR 2•23 and 1•50, respectively, GG v. AA). The GSTM1 and GSTT1 null genotypes were prevalent among 60•7 and 16•3 % of controls in the present study, which was consistent with the rate of GSTM1 null genotype (59•1 %), but much lower than that of GSTT1 null genotype (51•9 %) in Shanghai Women's Health Study (42) .…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of GSTP1 G allele was 18•1 % among controls in the present study. It was in accordance with the reported frequency of GSTP1 G allele from three studies in China (23,38,39) . Previous studies suggested that the functional mutation of the GSTP1 rs1695 polymorphisms may reduce the activity of GST-π enzyme deactivating and detoxifying carcinogens and thus may increase cancer vulnerability (40) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The C→T transition (rs700519) in exon 7 of the CYP19A1 gene leads to a single amino acid substitution, of Arg by Cys, at codon 264, and the T allele has been reported to enhance aromatase enzymatic activity, affecting the conversion of androgens. This modi cation may alter the risk of several disorders, such as breast cancer, polycystic ovary syndrome (PCOS), and endometrial cancer [36][37][38][39]. The current metaanalysis failed to detect any association between the Arg264Cys polymorphism and the overall PCa risk.…”
Section: Discussionmentioning
confidence: 57%
“…Поліморфізм GST У жінок з Китаю однонуклеотидний поліморфізм (SNP) GSTP1 Val105Ile (rs1695) асоціювався з підвищеним ризиком до раку молочної залози серед носіїв гетерозигот A/G та A/G+G/G, ніж у гомозиготних носіїв G/G порівняно з контролем A/A. Авторами була встановлена також різниця в асоціації між rs1695 та раком молочної залози серед білих, африканців та азіатів, що можна пояснити різними етнічними ознаками цих груп населення (Pan et al, 2016).…”
unclassified